Nanoimprinting of copper nanowires below 400°C - Lim, Zhan Xing (Nanyang Technological University, 2021)
Fabrication of one-dimensional metallic nanostructures are at upmost importance due to their distinct properties and high aspect ratio. Therefore, they have been of great demand in several industries. For example, nanostructures are used in healthcare as a drug delivery system to transport precise dosage to a desired location of the body. Nanostructures are also used in cosmetics like sunscreens for its transparent features. There are different Nano-fabrication methods to meet the market demand. However, they are restricted by high cost and long fabrication time. As a result, this project utilizes nanoimprinting via ultrasonic embossing to fabricate copper nanowires. During the project, it was observed that the geometry of nanowires is dependent on the welding force and amplitude of ultrasonic. With the addition of heat, vacuum and argon air, nanowires can be fabricated at a longer geometry.